Low EEG Gamma Entropy and Glucose Hypometabolism After Corpus Callosotomy Predicts Seizure Outcome After Subsequent Surgery - Kosugi, Kenzo; Iijima, Keiya; Yokosako, Suguru; Takayama, Yutaro; Kimura, Yuiko; Kaneko, Yuu; Sumitomo, Noriko; Saito, Takashi; Nakagawa, Eiji; Sato, Noriko; Iwasaki, Masaki (Frontiers in Neurology, 2022)
Background: Patients with generalized epilepsy who had lateralized EEG abnormalities after corpus callosotomy (CC) occasionally undergo subsequent surgeries to control intractable epilepsy. Objectives: This study evaluated retrospectively the combination of EEG multiscale entropy (MSE) and FDG-PET for identifying lateralization of the epileptogenic zone after CC. Methods: This study included 14 patients with pharmacoresistant epilepsy who underwent curative epilepsy surgery after CC. Interictal scalp EEG and FDG-PET obtained after CC were investigated to determine: (1) whether the MSE calculated from the EEG and FDG-PET findings was lateralized to the surgical side, and (2) whether the lateralization was associated with seizure outcomes. Results: Seizure reduction rate was higher in patients with lateralized findings to the surgical side than those without (MSE: p < 0.05, FDG-PET: p < 0.05, both: p < 0.01). Seizure free rate was higher in patients with lateralized findings in both MSE and FDG-PET than in those without (p < 0.05). Conclusions: This study demonstrated that patients with lateralization of MSE and FDG-PET to the surgical side had better seizure outcomes. Combination of MSE and conventional FDG-PET may help to select surgical candidates for additional surgery after CC with good postoperative seizure outcomes.